Social Aspects of Collaborative Learning in Virtual Learning Environments - Laister, Johann; Kober, Sandra (Proceedings of the International Conference on Networked Learning, 2002)
This paper gives an overview on new practical approaches in e-learning focussing on collaborative learning and therefore also on social components of learning. Collaborative learning which presently mainly takes place in physical meetings is described closer by figuring out advantages and critical points. In addition social aspects of learning with a special focus on communication/interaction are described. Thus, collaborative learning is a theoretical background of learning communities a brief overview on virtual learning communities and basic community requirements is given. Examples from progressing projects and research are showing how we try to implement collaborative virtual learning environments by taking into consideration social factors of e-learning.